A Comparative Clinical Study In The Management Of Vicharchika - Sharma, Gaurav; Raju, M D P; Pachchinavar, K H; Yakkundi, R C; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2020)
Eczema or dermatitis is an inflammatory response of the skin to multiple agents, characterized by erythema, edema, vesiculation, oozing, crusting and later lichenification. Charka describes ‘Vicharchika’ under Kshudrakustha with the lakshanas Kandu, Shyavapidaka and Bahusrava. Authors like Yogratnakara, Madhavkara and Vangasena too referred the same features. According to Sushruta the lakshanas are Rajyo, Atikandu, Ruja, and Rukshata involving the domination of Pitta. In Ayurvedic classics there is an elaborative treatment for vicharichika, which includes both shodhana & shamana chikitsa. In this study, comparison of efficacy of Siravyadhana and Karnja Taila application on vicharchika is studied. Total 60 patients of Vicharchika (eczema) were registered for the present study. They were randomly divided into two groups of 30 each. Group A was given Required quantity for external application twice daily, half an hour before bath & half an hour before bed time. In group B, 2 seating of Siravedhana karma was carried out on every 15 days followed by application of Karanja taila twice daily. Amount of Blood letting was decided after measuring one Anjali fulfilled by water in every patient. Results: After the study it is revealed that the Siravedhana followed by application of Karanja Taila is having good results in Vicharchika.